Kehilangan Identitas di Tengah Krisis Moralitas Masyarakat Indonesia - Agung Priyadi Tahaku (STAI DDI Kota Makassar, 2020)
The development of an increase in ethnic diversity in an area began since Indonesia's independence through a massive transmigration program even to all islands outside Java. The method used is descriptive method, as an activity that involves data in the framework of research or answering questions related to the current situation of the subject of a study. (1), General Review of Life without Identity (2) General Review of Morality Crisis (3) Overview of Higher Education, society has not been able to identify as wealth in diversity, in the results of interviews and observations in the Review, most adolescents are vulnerable to promiscuity, this condition is also influenced by early moral education to build moral sensitivity of the nation's children. The values ​​of life as norms in society are always a matter of problems between good and bad, so there is something to do with morals, so that education with intellectuality must be in line with the moral care of the nation's children, in this way identity will become wealth in diversity.